EFFECT OF RAMIAL FRAGMENTED WOOD AMENDMENTS ON THE GERMINATION RATE (%) OF DURUM WHEAT - Kerrouche, I; Bazri, K.E.M; Zeltni, A.E.S; Ouahrani, G (university of el oued/جامعة الوادي, 2021)
The presence of organic matter in agricultural soils is an important factor in assessing the conditions of the soils. BRF and Manure are energy inputs that can improve the soil. The objective of our work is to study the influence of the contribution of Rameal Fragmented Wood (RFW) and cattle manure in the presence and absence of earthworms Octodrilus complanatus on the germination rate (%) of durum wheat (Tritucum durum) of the Hedba 3 variety. The study station is located in a semi-arid zone (Constantine, Algeria). the results obtained show that the contribution of RFW or RFW mixture and cattle manure in the presence and absence of earthworms Octodrilus complanatus has a beneficial effect on the the germination rate increased by 193.35% on average in the amended plots compared to the control plots
Article
Keywords: Keywords: Constantine; Rameal Fragmented Wood (RFW); Cattle manure; Octodrilus complanatus; germination rate.